Good Readers Are Good Thinkers - Dianti, Rahma; Pamuji, Arif (UNIVERSITAS TRIDINANTI PALEMBANG, 2016)
ABSTRACT: This article highlights the relationship between reading activity and thinking skill, and to expose the impacts of reading comprehension toward someone’s thinking skill and vice versa. Reading involves cognitive process. A reader can process the text during reading activity while she or he thinks over what stated in the passage to comprehend the text. Comprehension is the reason for reading. If readers can read the words but do not understand fully what the meaning of the text being read, they are not really reading. The reading itself involves thinking. It takes place when a reader recognizes printed symbols, interprets the prints, and responds by saying the words and gets meaning from the process of reading. When reading, good readers usually go beyond the line and interpret what is written in the light of the context of their own experiences, select the ideas that are pertinent to the purposes for reading, evaluate them, compare them with the available facts, and reach tentative conclusions or generate new ideas. Therefore, reading is a cognitive process. EFL students who read routinely and critically must significantly expand their insights about the world, which lead them to be broad minded. Furthermore, to be critical thinkers, the students must firstly be avid readers.